MENTORSHIP DALAM PENGEMBANGAN SUSTAINABILITY BUSINESS USAHA KRIPNAS (KERIPIK NASI) - Hapsari, Yua Sahara Suci (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This study examines the role of mentorship in developing sustainability-oriented business practices at Kripnas (Rice Chips) as a food-based MSME. Mentorship plays an important role in transferring knowledge, sustainability values, and responsible business practices to support long-term business continuity. Using a qualitative case study approach based on business documentation, observations, and MBKM internship reports in 2025, the study finds that mentorship contributes to strengthening human resource capacity, improving business awareness, and reinforcing sustainable production and marketing practices. The results highlight that continuous mentorship is a key factor in supporting the sustainability of MSMEs such as Kripnas.